Prevalence and Characteristics of Intracranial Hemorrhages in Neonates with Hypoxic Ischemic Encephalopathy - Bashir, Rani A.; Vayalthrikkovil, Sakeer; Espinoza, Liza; Irvine, Leigh; Scott, James; Mohammad, Khorshid (American Journal of Perinatology, 2018)
Introduction The risk factors of intracranial hemorrhages (ICH) in the context of neonatal hypoxic ischemic encephalopathy (HIE) and related interventions are unclear.Objective This article examines the prevalence and risk factors associated with ICH in neonates with HIE.Study Design This is a retrospective cohort study of neonates with HIE in Southern Alberta. ICH (subdural [SDH], subarachnoid [SAH], intraventricular [IVH], intraparenchymal [IPH]) were diagnosed by magnetic resonance imaging (MRI). Perinatal and neonatal characteristics were examined. Relation of hemorrhages with hypoxic changes on MRI and HIE stages were assessed.Results Number of HIE patients, n = 157; brain MRI was done in 138 infants; median gestation, 40 weeks; and cooled = 103 (66%). Prevalence of SDH, IPH, IVH, and SAH were 47, 22, 11, and 10 (34.1%, 15.9%, 7.8%, 7.2%), respectively. There was no significant increase in hemorrhage with mode of delivery, seizures, hypo/hypercarbia, severe thrombocytopenia, or deranged coagulation. All hemorrhages increased with higher HIE stage, regardless of the HIE severity in MRI. Adjusting for HIE staging, cooling, and gestation, IPH was observed more in infants who received inotropes (odds ratio [OR], 3.32; 95% confidence interval [CI], 1.20, 9.20).Conclusion SDH followed by IPH were the most common ICH. Thrombocytopenia and deranged coagulation did not increase risk of hemorrhages in HIE. Our study was not powered to determine the impact of inotrope use on the risk of IPH.
Keywords: HIE; hemorrhage; coagulopathy; thrombocytopenia; neonate